An ANALYSIS OF WRITTEN ERROR AMONG EFL STUDENTS OF ENGLISH PROFICIENCY LEVEL OF INTERNATIONAL PROGRAM - Suhono, Suhono (Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia, 2016)
This study aims at providing a comprehensive account of analyzing error in second language learners. For this purpose, an empirical study was conducted, using Indonesian students learning English as the research subject, especially among students of international program of Muhammadiyah University Surakarta. The researcher explored the type of errors made by students at different proficiency levels: high, medium, and low level. This study uses error analysis as methodological framework. More specifically, this study was an attempt to describe the type of grammatical error which frequently exist in written production, to describe frequency grammatical error among proficiency levels, and to describe the students’ understanding of errors. Students’ writings were analyzed for errors based on surface strategy taxonomy. The results of this research revealed that 846 sentences indicated errors. Types of omission error was the highest one 322 (37.9%) sentences. Afterward, grammatical error in low proficiency level was the highest one 322 (37.9%) sentences. The second was high proficiency level 276 (32.6%) sentences. The third was medium proficiency level 248 (29.3%) sentences. Most of the students didn’t understand about grammatical errors, because through students’ interview only 7 students were able to change grammatical error to be good sentences.